Theoretical and practical substantiation for prediction of equivalent dose rate of gamma radiation at the Sukhachivske tailings storage facility I section - Korotaiev, Volodymyr; Bielikov, Anatolii; Pylypenko, Oleksandr; Podkopaiev, Serhii; Tkachuk, Oleksandr; Shalomov, Volodymyr (Technology audit and production reserves, 2024)
The object of the study is the Sukhachivske industrial site, tailings storage facility section I (Ukraine). The main reason for conducting the study is to establish actual and forecast numerical values of absorbed and exposure dose rates. The state of radiation contamination of the tailing’s storage facilities of the Sukhachivske industrial site was analyzed. The actual and prolonged levels of equivalent dose rate, absorbed dose rate, and total personnel exposure dose were determined. Dependencies were established that allow determining approximate numerical values for specific conditions and certain areas using the finite element method with subsequent transfer of values to 2024–2027. Based on the conducted studies, the dynamics of contamination at the Sukhachivske tailings storage facility section I was predicted. The estimated, forecast, and actual values of personnel exposure doses were determined for the period from 2010 to 2023. New methods and algorithms for instrumental measurement of radiation parameters at the tailing’s facilities of the former uranium production facility of the Prydniprovsky Chemical Plant have been developed. The state of radiation contamination of the tailing’s facilities of the Sukhachivke industrial site has been analyzed. The actual and prolonged levels of equivalent dose rate, absorbed dose rate, total personnel exposure dose, and contamination levels of the territories adjacent to the tailings facilities have been determined. Monitoring studies over ten years have allowed to determine the actual values of the exposure dose rate, which range from 0.08 to 0.21 μSv/h with certain local values up to 0.26 μSv/h. In general, the total personnel exposure dose does not exceed 1.1–1.4 mSv/year. The obtained data on prognostic values, in turn, make it possible to predict the further radiation situation at the Sukhachivske industrial site in the coming years. As well as to improve the system for calculating the total effective radiation dose, both to the personnel of the radiation-hazardous facility and to the population living near the industrial site.